1993
DOI: 10.1128/mcb.13.5.2677-2687.1993
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Recognition of a Vertebrate Mini-Exon as an Exon-Intron-Exon Unit

Abstract: Very small vertebrate exons are problematic for RNA splicing because of the proximity of their 3' and 5' splice sites. In this study, we investigated the recognition of a constitutive 7-nucleotide mini-exon from the troponin I gene that resides quite close to the adjacent upstream exon. The mini-exon failed to be included in spliced RNA when placed in a heterologous gene unless accompanied by the upstream exon. The requirement for the upstream exon disappeared when the mini-exon was internally expanded, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Small exons (~60 nts or less) have been associated with poor inclusion in messenger RNAs [ 16 , 17 , 18 , 19 ]. This length limit also applies to constitutively spliced internal exons, which have an optimal size range between 60 and 200 nts [ 19 ].…”
Section: Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…Small exons (~60 nts or less) have been associated with poor inclusion in messenger RNAs [ 16 , 17 , 18 , 19 ]. This length limit also applies to constitutively spliced internal exons, which have an optimal size range between 60 and 200 nts [ 19 ].…”
Section: Hypothesismentioning
confidence: 99%
“…This length limit also applies to constitutively spliced internal exons, which have an optimal size range between 60 and 200 nts [ 19 ]. Although smaller exons may lack cross-exon interactions with spliceosomal components, many mini- or even micro-exons are efficiently recognised in vivo in a constitutively or alternatively spliced manner [ 17 , 20 ]. Such exons are often located very close to additional exons upstream or downstream that are separated by short introns withregulatory functions [ 17 ].…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Additional pioneering work contributed to the microexon splicing network and this consisted of the work of Sterner and Berget (1993), who initially utilized microexon (7 nt) from Troponin I gene and identified that the upstream exon was required for inclusion of microexon (Sterner & Berget, 1993). In subsequent studies, they used the microexon (6 nt) from the chicken cardiac troponin gene and showed that an intron splicing enhancer element (ISE) containing G‐rich sequence was essential for microexon inclusion.…”
Section: The Architecture Of the Microexon And Its Neighboring Sequencesmentioning
confidence: 99%